Prevalence and profile of headache in school-going adolescents aged 10 – 19 years in Benin City: a cross sectional survey - Ikhurionan, Paul; Mbarie, Imuwahen (Headache Medicine, 2024)
IntroductionAdolescent headaches significantly impact their daily functioning, academic performance, and quality of life. The occurrence of headaches is influenced by genetics, psychological stressors, and environmental exposures. Understanding these influences is crucial for effective management strategies.AimTo determine the prevalence, characteristics, and associated factors of headaches among school-going adolescents in Benin City, Nigeria.MethodsThis was a descriptive cross-sectional study among secondary school students. Using a structured questionnaire, data on sociodemographics, headache characteristics, triggers, and impacts were collected. The chi-square test was used to assess the association between the presence of headaches and categorical covariates. All analyses used a significance level of p